EP 39. Clinical experience with deep brain stimulation in Huntington's disease. Issue 9 (September 2016) - Rasche, D.; Zittel, S.; Tadic, V.; Moll, C.; Fellbrich, A.; Brüggemann, N.; Bäumer, T.; Tronnier, V.; Münchau, A.
Abstract : Introduction: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) or globus pallidus internus (GPi) are well-established standard procedures for various movement disorders, e.g. Parkinson's disease or dystonia. Until now, application of DBS in Huntington's disease (HD) has been performed only as an individual and experimental treatment option reported in a few cases. Objective: We present a prospective controlled case series of six patients with HD and bilateral DBS of the GPi. Material and Methods: Indication for DBS was stated in six patients with severe, treatment-refractory chorea. The procedure was performed in general, intravenous anaesthesia. Bilateral lead placement in the GPi was achieved with stereotactic MRI-coordinates and intraoperative microrecordings. Stereotactic coordinates were as follows: (x) 19–20 mm lateral the midline of the intercommissural line, (y) 3 mm anterior and (z) 2–3 mm inferior the midpoint of the intercommissural line. Also intraoperative stimulation via the implanted leads was performed to evaluate stimulation induced-side effects like dystonic movements, eye movements etc. After insertion of the leads a second stereotactic MRI was performed to rule out any intracerebral complications and to document the definite position of the lead. Clinical evaluation included the motor score of the Unified Huntington's disease rating scale (UHDRS), Total Functional Capacity score (TFC), the Functional Assessment score (FA) and the 26-item version of the World Health Organisation questionnaire (WHO Bref) preoperatively and six months postoperatively. Results: In all 6 patients leads were successfully implanted bilaterally in general anaesthesia. In one case one lead needed to be revised due to dislocation detected in the control, second MRI. Also in one case, second MRI revealed a small local haemorrhage in the course of one lead, but no clinical neurological deficits were observed in the patient postoperatively. Standard stimulation parameters were programmed and adjusted individually (mono- or bipolar mode, 30–130 hertz, 50–100 microseconds, amplitude 2–5.0 milliampere). The chorea subscore of the UHDRS motor score improved by 47% (range 21–86%; p  < 0.01). UHDRS total motor score was reduced by 17% ( p  = 0.02). Dystonia and bradykinesia subscores remained unchanged. Antihyperkinetic medication could be reduced in all of the patients. TFC and FA did not show an improvement in activities of daily living. Six months postoperatively, the WHO Bref total score increased from 207.89 ± 21.91 to 277.61 ± 37.39 ( p  = 0.02). There was a significant improvement in domain 2 (psychological) (47.92 ± 7.98 vs. 77.08 ± 12.96, p  < 0.01) and domain 4 (environment) (53.13 ± 9.20 vs. 79.69 ± 5.98, p  < 0.01). Conclusion: DBS of the GPi is an additional invasive treatment option for well-selected patients with HD. Risks and complications of the procedure and related to the implanted materials are low and acceptable. Continuous clinical experience and long-term follow-up of these patients are needed to evaluate the significance and evidence of DBS in HD.